Turbulent stress measurements with phase-contrast magnetic resonance through tilted slices - MacKenzie, Jordan; Söderberg, Daniel; Swerin, Agne; Lundell, Fredrik (Experiments in fluids, 2017)
Aiming at turbulent measurements in opaque suspensions, a simplistic methodology for measuring the turbulent stresses with phase-contrast magnetic resonance velocimetry is described. The method relies on flow-compensated and flow-encoding protocols with the flow encoding gradient normal to the slice. The experimental data is compared with direct numerical simulations (DNS), both directly but also, more importantly, after spatial averaging of the DNS data that resembles the measurement and data treatment of the experimental data. The results show that the most important MRI data (streamwise velocity, streamwise variance and Reynolds shear stress) is reliable up to at least r ¯ = 0.75 without any correction, paving the way for dearly needed turbulence and stress measurements in opaque suspensions.